Sistem Informasi Peternakan Sebagai Pengembangan Media Promosi Pada Arjuna Farm Berbasis Web - Nasution, Adnan Buyung (Jurnal Media Informatika, 2024)
Information technology has become a primary need in various sectors, including UMKM. Arjuna Farm focuses on goat and sheep farming. Arjuna Farm provides services such as Aqiqah, Qurban, goat milk, and educational tour programs. Arjuna Farm faces limitations in promoting their services and products through social media platforms such as Instagram and Facebook. Therefore, a web-based information system is needed to promote services at Arjuna Farm. Through this research, an information system was developed to assist in promotion, product sales, and farm services. The system development method used is Rapid Application Development (RAD). The research results show that this system serves as a platform for promotion and services at Arjuna Farm, providing ease for users in ordering products and reserving educational services.